2011
DOI: 10.1038/aps.2011.88
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of irbesartan and amlodipine on hemodynamic amelioration and organ protection in spontaneously hypertensive rats

Abstract: Aim: To investigate the synergism of low-doses of amlodipine and irbesartan on reduction of blood pressure variability (BPV), amelioration of baroreflex sensitivity (BRS) and organ protection in spontaneously hypertensive rats (SHR). Methods: The rats were administered amlodipine (1 mg·kg -1 ·d -1 ) alone, irbesartan (10 mg·kg -1 ·d -1 ) alone, or the combination of the two drugs for 4 months. The drugs were mixed into the rat chow. Blood pressure (BP) was continuously monitored in conscious animals. After the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…BP and heart rate were continuously recorded in conscious, freely moving rats as previously described (Liu et al 2013, Yu et al 2013, Shang et al 2011. Briefly, 4 weeks after SAD or sham operations, rats were anesthetized with pentobarbital sodium and a floating catheter (PE10; Biotrol, Paris, France) was inserted into the lower abdominal artery via the left femoral artery; another catheter (PE50) was inserted into the left femoral vein for intravenous injection.…”
Section: Hemodynamic Monitoring Of Conscious Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…BP and heart rate were continuously recorded in conscious, freely moving rats as previously described (Liu et al 2013, Yu et al 2013, Shang et al 2011. Briefly, 4 weeks after SAD or sham operations, rats were anesthetized with pentobarbital sodium and a floating catheter (PE10; Biotrol, Paris, France) was inserted into the lower abdominal artery via the left femoral artery; another catheter (PE50) was inserted into the left femoral vein for intravenous injection.…”
Section: Hemodynamic Monitoring Of Conscious Ratsmentioning
confidence: 99%
“…After a 14 h habituation, beat-to-beat BP and heart period (HP) values were acquired online for 24 h. Offline analysis was performed to obtain related hemodynamic parameters. The beat-to-beat BP mean values were used as indexes of BP and the standard deviations of beat-tobeat BP values as indexes of BPV (Liu et al 2013, Yu et al 2013, Shang et al 2011.…”
Section: Hemodynamic Monitoring Of Conscious Ratsmentioning
confidence: 99%
“…By multiple regression analysis, Shang et al have found that the reduction in BPV induced by the chronic administration of irbesartan and amlodipine contributes to ameliorate left ventricular hypertrophy and renal lesion in spontaneously hypertensive rats [74]. In another report, the effect of chronic administration of different antihypertensive drugs on target organ damage was studied in spontaneously hypertensive rats.…”
Section: Preclinical Evidencementioning
confidence: 99%
“…Ghrelin, a neuropeptide originally known for its growth hormone-releasing and orexigenic properties and which exerts important pleiotropic effects on the cardiovascular system, has also been shown to increase baroreflex gain in healthy individuals [51]. Particular combination of known antihypertensives can also sensitize baroreflex, probably following blood pressure reductions [52].…”
Section:  Scientific Rationalementioning
confidence: 99%